(untitled) (European Journal for Qualitative Research in Psychotherapy, 2020)
This paper aims to examine and de-mystify the process of writing a journal article. It recommends a structured, systematic approach involving four stages: thinking, planning, writing, and manuscript creation. Detailed ‘how to’ steps are suggested for each stage, always with an emphasis on the dynamic movement between thinking/planning and revising/developing. The process described is one where the author gradually shapes and constructs their article through its different incarnations. A key suggestion is that writers concentrate on drafting shorter, more manageable sections, rather than attempt to write an article all the way through from beginning to end. Novice writers are offered tips on how to structure articles and free up their writing process. They are also reminded to attend carefully to the requirements and house style of the journal, as well as to the needs and interests of readers. Interspersed throughout is a personal, reflexive, autobiographical account of my own process during the moment-by-moment construction and development of this article.